2015
DOI: 10.1186/s12886-015-0168-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of pupil dilation on spectral-domain optical coherence tomography measurements and their quality score

Abstract: BackgroundSpectral-domain optical coherence tomography (SD-OCT) provides fast scan speed and high scan resolution improving its diagnostic accuracy. The purpose of this study was to evaluate if SD-OCT measurements and their quality score are influenced by pupil dilation.MethodsRetinal nerve fiber layer thickness (RNFL), ganglion cell complex (GCC) and optic nerve head (ONH) were measured in one eye of 57 glaucoma patients and 36 healthy subjects using spectral domain optical coherence tomography (SD-OCT) befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Before imaging, all subjects with ACHM were dilated using either a single drop of cyclomydril (cyclopentolate hydrochloride [0.2%] and phenylephrine hydrochloride [1%]) or a combination of tropicamide (1%) and phenylephrine hydrochloride (2.5%) for cycloplegia and pupillary dilation. Control subjects were imaged without dilation, as a previous study evaluated layer thickness measurements before and after dilation and found no change 30. The Bioptigen spectral domain OCT (Leica Microsystems, Wetzlar, Germany) was used to acquire transfoveal line and/or volume scans in both eyes of each subject.…”
Section: Methodsmentioning
confidence: 99%
“…Before imaging, all subjects with ACHM were dilated using either a single drop of cyclomydril (cyclopentolate hydrochloride [0.2%] and phenylephrine hydrochloride [1%]) or a combination of tropicamide (1%) and phenylephrine hydrochloride (2.5%) for cycloplegia and pupillary dilation. Control subjects were imaged without dilation, as a previous study evaluated layer thickness measurements before and after dilation and found no change 30. The Bioptigen spectral domain OCT (Leica Microsystems, Wetzlar, Germany) was used to acquire transfoveal line and/or volume scans in both eyes of each subject.…”
Section: Methodsmentioning
confidence: 99%
“…However, dilation is not necessary to get good OMAG signal (unpublished data). Overall, the pupil size does not affect the signal strength of OCT signal 41 , 42 as well as OMAG flow signal (unpublished data).…”
Section: Discussionmentioning
confidence: 87%
“…Prior to imaging, all patients with ACHM were dilated using either cyclomydril or a combination of tropicamide (1%) and phenylephrine hydrochloride (2.5%) for cycloplegia and pupillary dilation respectively. Control patients were imaged without dilation, as a previous study evaluated layer thickness measurements pre- and post-dilation and found no change 32 . The Bioptigen spectral domain-OCT (Leica Microsystems, Wetzlar, Germany) was used to acquire line scans at the fovea in both eyes of each subject.…”
Section: Methodsmentioning
confidence: 99%